2007
DOI: 10.1111/j.1526-4610.2007.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Deficiency and Response to Supplementation in Pediatric and Adolescent Migraine

Abstract: Deficiency of CoQ10 may be common in pediatric and adolescent migraine. Determination of deficiency and consequent supplementation may result in clinical improvement. Further analysis involving more scientifically rigorous methodology will be required to confirm this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(98 citation statements)
references
References 39 publications
1
89
0
3
Order By: Relevance
“…The authors showed that responders were 47.6% in the CoQ 10 treated group vs 14.4% in the placebo group. A positive effect of CoQ 10 was also demonstrated in a large group of pediatric patients suffering from migraine (Hershey et al, 2007).…”
Section: Neurodegenerative Diseasementioning
confidence: 73%
“…The authors showed that responders were 47.6% in the CoQ 10 treated group vs 14.4% in the placebo group. A positive effect of CoQ 10 was also demonstrated in a large group of pediatric patients suffering from migraine (Hershey et al, 2007).…”
Section: Neurodegenerative Diseasementioning
confidence: 73%
“…30,[34][35][36][37] Based on emerging evidence, some clinicians also recommend dietary supplements that decrease inflammation (omega-3 fatty acids) and dietary supplements, such as riboflavin, magnesium, and coenzyme Q10. [38][39][40][41][42][43][44] However, some clinicians are not familiar with these therapies; therefore, they do not use them and do not inquire about them. So, little is known about the extent of their impact or use by their patients who experience HA.…”
Section: Resultsmentioning
confidence: 99%
“…Determination of deficiency and consequent supplementation may result in clinical improvement. Further analysis involving more scientifically rigorous methodology will be required to confirm all those observations in any way [112].…”
Section: Miscellaneousmentioning
confidence: 99%